If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(14g + 2) = 6(3g + -5) Reorder the terms: 2(2 + 14g) = 6(3g + -5) (2 * 2 + 14g * 2) = 6(3g + -5) (4 + 28g) = 6(3g + -5) Reorder the terms: 4 + 28g = 6(-5 + 3g) 4 + 28g = (-5 * 6 + 3g * 6) 4 + 28g = (-30 + 18g) Solving 4 + 28g = -30 + 18g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-18g' to each side of the equation. 4 + 28g + -18g = -30 + 18g + -18g Combine like terms: 28g + -18g = 10g 4 + 10g = -30 + 18g + -18g Combine like terms: 18g + -18g = 0 4 + 10g = -30 + 0 4 + 10g = -30 Add '-4' to each side of the equation. 4 + -4 + 10g = -30 + -4 Combine like terms: 4 + -4 = 0 0 + 10g = -30 + -4 10g = -30 + -4 Combine like terms: -30 + -4 = -34 10g = -34 Divide each side by '10'. g = -3.4 Simplifying g = -3.4
| 12(2c+10)=3(13c-7) | | 2(12h+6)=12(6h-3) | | 5(11d+10)=5(9d-1) | | 12x-130=4x-10 | | 7+91x=52x+25 | | -2x+4x=-4+10x | | 7x-1/4-1/3[2x-(1-x/20=19/3 | | 8(3w-9)=2(3w+9) | | 7x-1/4-1/3[2x-1-x/2=19/3 | | 8(3f-9)=2(3w+9) | | 6x-12y+18z= | | 2/3*(5x-2)-(4x(-1-3x)/2)=(5x-11)/2 | | (X-2)(x-6)=2x-13 | | 3(4f-8)=3(3f+1) | | 3(4u-8)=3(3f+1) | | 2(7s+6)=3(8s+4) | | 3(7w+6)=3(2w+3) | | 3(3c-2)=4(6c+3) | | X^2+13=15 | | 7p+5=4+11 | | b^2+2b+6b+12= | | (13+x)+x=97 | | 2+3a=7.4 | | 10+2a=-2 | | 7=1-2a | | 5a-7=4 | | 4(4u+2)=3(2u+1) | | 2.4=3a-1.2 | | 16=7a-1 | | x/18=7/10 | | 3a+1=11 | | 5a+1=4.5 |